Medical records management in HUKM Medical Records Department : a case study / Fakhurrazi Ibnu Omar - Ibnu Omar, Fakhurrazi (2005)
Medical records growth can be considered as one of the trade off in community development. Number of new patient register, tell that there are increasing number of community member, whereas particular cases tendency will show the pattern and lifestyles of the community. Medical record as individual physical, mental health valid evidence in presenting his well being, treatment, defect and the assessment received from medical practitioner. The issue of privacy in medical records has long been a trademark, even not a patient should know their own. Medical records not only serve as patient medical history, but will be used later in many legal related activities such as insurance claim, evidence in court, as valid evidence in employee leave, benefit claim and exemption. Records management practice in any field is necessary in pursuance of a good, quality records keeping. Intention is to provide the records when needed as possible. All elements in records management give prior attention into all aspect of records safekeeping- how to measure the growth, the location, to separate into different group and so on. This study conducted in attempt to documenting the practiced Medical Records Management in HUKM Medical Records Department. There are few local content on the subject done by people with medical background himself. This writing from records management side into medical records treatment will just add variety into a wide understanding of medical records management to understand the program in work setting. The scopes are all patient medical records, specifically the medical records files, element of records management such as inventory, appraisal and retention, vital records, disaster planning and recovery, form management, directives management, report management, active record system, records storage and records disposition studied and investigated over their practiced. Standard research methodologies used in gathering the information, such as structured interview, structured distribution of questionnaires, existing document review. During the study, observation being made on the working area, storage equipment and the handling process. Medical has always paid high concern, on keeping safe the medical records, as it among legal and professional requirement in their field. Case study HUKM Medical Records Department, presented understanding the program implementation. Moreover, any additional knowledge hoped to be harvested, and recorded in this study. From the study it can be concluded HUKM as parent organization recognized the function of Medical Records Department as core service supportive element. Medical Records Department itself, seriously undergone service overhaul timely to increase the service capability, procedure manner to in line with organization objective. Long waiting time for patient appointment with doctor that become a critics recently trigger the alarm for reviewing the element contribute to the matter.